Restoring the Midlands of Tasmania: An introduction. (30th December 2021) - Davidson, Neil J.; Bailey, Tanya G.; Burgess, Sebastian
Summary: At the dawn of the Anthropocene, with the imminent threat of climate change delivering 3–4°C rise in temperature by the end of the century and biodiversity loss across the globe, restoration projects need to focus on re‐establishing connectivity in vegetation structure at a landscape scale to facilitate the movement of wildlife. To achieve this requires long‐term commitment, robust partnerships and planning and excellent planting technology underpinned by research. In this Special Issue, consisting of 15 papers, we present a multidisciplinary, multi‐institutional, science‐based approach to environmental restoration, focused on a single geographic region, the Midlands of Tasmania. This introductory paper describes the breadth of the material covered in the series and sets the scene for following papers by describing the Midlands, its geography, climate and history, its extraordinary natural values as a biodiversity hotspot, the degree of degradation that has resulted from 200 years of intensive farming and the objectives of the Midlands restoration project. The Midlands also offers opportunities as a model system for landscape scale restoration given it is a circumscribed region, heterogeneous in land forms and land uses. Furthermore, in land management, there is a high level of cooperation between land owners, government departments, environmental agencies and university researchers. We describe how the contributions from a wide range of disciplines can be focused to meet the challenges of ecological restoration in highly altered agricultural landscapes.